2002
DOI: 10.1053/eujp.2002.0341
|View full text |Cite
|
Sign up to set email alerts
|

Pain‐related fear in acute low back pain: the first two weeks of a new episode

Abstract: The overall aim of this study was to explore the natural course of pain-related fear during the early stage of a new low back pain episode, using a prospective case series design. Specific research questions addressed the existence of typical patterns in individual time series of pain-related fear and sequential relationships between the occurrence of pain-related fear, pain and pain catastrophizing. Forty-four general practice patients who consulted their physician with a new episode of non-specific low back … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
55
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(66 citation statements)
references
References 26 publications
8
55
0
2
Order By: Relevance
“…Consistent with this model, acute and chronic low back pain patients with high pain-related fear typically show submaximal performance on a variety of physical challenges such as straight leg raise, knee-extension-flexion, trunkextension-flexion, and weight lifting [1,2,5,7,11,12,16,30,34,38,41]. These findings suggest that performance during forward bend tasks, as measured by thoracic, lumbar and hip excursions, may be influenced by individual differences in pain-related fear.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Consistent with this model, acute and chronic low back pain patients with high pain-related fear typically show submaximal performance on a variety of physical challenges such as straight leg raise, knee-extension-flexion, trunkextension-flexion, and weight lifting [1,2,5,7,11,12,16,30,34,38,41]. These findings suggest that performance during forward bend tasks, as measured by thoracic, lumbar and hip excursions, may be influenced by individual differences in pain-related fear.…”
Section: Introductionsupporting
confidence: 53%
“…1 The effects of group and day on the peak to peak joint excursions of the lumbar spine are depicted PASS, TSK, and PCS), suggesting a robust and potentially important clinical finding. Although pain-related fear has previously been related to submaximal performance on a variety of physical challenges [1,2,5,7,11,12,16,30,34,35,38,41] a unique feature of this study is a mapping of this construct to joint movements during performance of a routine assessment procedure for patients with low back pain. Specifically, at each testing session participants with high levels of fear displayed less lumbar flexion during forward bending, even after statistically controlling for pain.…”
Section: Discussionmentioning
confidence: 99%
“…191, 296, 302 Prospective studies suggest fear-avoidance beliefs are predictive of the development of chronic low back pain. 108, 109, 177, 268 As a result, identification of elevated fear-avoidance beliefs has been suggested to as an important component in the assessment of low back pain. The Fear-Avoidance Beliefs Questionnaire (FABQ) is commonly used to assess fear-avoidance beliefs in patients with LBP and has physical activity (FABQ-PA) and work (FABQ-W) scales.…”
Section: Clinical Guidelines: Examinationmentioning
confidence: 99%
“…2,4,22 In addition, several longitudinal studies indicated that elevated pain-related fear is a precursor to poor clinical outcomes. 7,13,20 In my opinion, the FAMEPP has had a meaningful impact on the study of musculoskeletal pain because it clearly hypothesized that elevated pain-related fear and associated avoidance were not adaptive responses and, in fact, had the potential to significantly contribute to the development and maintenance of chronic pain and disability. …”
mentioning
confidence: 99%